The Potential of Landfill Waste in Rembang City as Raw Material for Refuse Derived Fuel (RDF) - Okmi Hapsari; Syafrudin Syafrudin; Mochamad Arief Budihardjo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
The Landoh landfillwas expired in 2022 due to the increasing amount of waste generated. The solution is to extend the service life of the landfill using the landfill mining method. The waste in the landfill is used as raw material for refuse derived fuel (RDF). The aim of the research is to find out the potential of landfill mining at Landoh landfillwhether it can be used as raw material for RDF. Primary data was taken from Landoh landfill in February 2022 with a depth of 1-2 meters and 3-4 meters from the surface of the waste generation and interviews with landfill officials. The waste samples were analyzed for waste composition, moisture content, volatile content, ash content and heating content. The waste composition is dominated by organic waste which has a large moisture content but a small caloric content. From the results of the research that the waste needs to be pre-treated (chopping and drying) for 21 days in order to fulfil the standard values of moisture content, volatile content, ash content and calorific content according to RDF raw material requirements. This method is a solution to overcoming expired landfills, reducing the volume of waste and landfill area requairements.